-2(6-2n)=5(n-1)

Simple and best practice solution for -2(6-2n)=5(n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(6-2n)=5(n-1) equation:


Simplifying
-2(6 + -2n) = 5(n + -1)
(6 * -2 + -2n * -2) = 5(n + -1)
(-12 + 4n) = 5(n + -1)

Reorder the terms:
-12 + 4n = 5(-1 + n)
-12 + 4n = (-1 * 5 + n * 5)
-12 + 4n = (-5 + 5n)

Solving
-12 + 4n = -5 + 5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5n' to each side of the equation.
-12 + 4n + -5n = -5 + 5n + -5n

Combine like terms: 4n + -5n = -1n
-12 + -1n = -5 + 5n + -5n

Combine like terms: 5n + -5n = 0
-12 + -1n = -5 + 0
-12 + -1n = -5

Add '12' to each side of the equation.
-12 + 12 + -1n = -5 + 12

Combine like terms: -12 + 12 = 0
0 + -1n = -5 + 12
-1n = -5 + 12

Combine like terms: -5 + 12 = 7
-1n = 7

Divide each side by '-1'.
n = -7

Simplifying
n = -7

See similar equations:

| 4(W+1)-7=3(7-1)+W | | 5x+8x-40=80-7x | | 4(6+7)=4*6+x*7 | | s=-16t^2+128t+144 | | 18xy-3x-19xy= | | 24x^2+91x+72=0 | | 5G/7=18 | | -14.1+18.3= | | 4x+9=12+3x | | -7/2-2x=-1/2 | | ((4x^2)-2x+6)/(2x-3) | | 65-7x=2x+23 | | -5(k+3)+4k=3(k-5) | | 80=5*2b | | -2-(6)= | | 25x+30y=120 | | .1(.1x+.9)= | | 3y=3y+18 | | -6(x-2)=12-3x | | 15+6x=25+5x | | 5x-2(-x-6)=-37 | | x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 |

Equations solver categories